IMPLEMENTASI PENDEKATAN SAINTIFIK MATA PELAJARAN IPS PADA FORUM GURU AMBARAWA (Universitas Negeri Semarang, 2018)
Abstract The scientific approach is one of the recommended learning approaches in the implementation of the 2013 Curriculum. In the practice of learning, the use of a scientific approach is carried out by learning steps known as 5M learning strategies which consist of: observing, asking questions, collecting data, associating, and communicate (Permendikbud. No. 22 of 2016). The learning strategy trains students to carry out learning activities as scientists develop knowledge, although not all science is developed in this way. The discussion between the proposers of service with partners is the Ambarawa teacher forum to solve the problem, then the problem solving will be carried out. Problem solving will be carried out, namely by implementing community service with the title Implementation of the Scientific Approach to Social Studies Subjects at the Ambarawa Teacher Forum. Starting from the identification of the problem the following problems were formulated: (1) How to train teachers to design learning programs with scientific approaches and 5M learning strategies? (2) How to train teachers to implement learning with a scientific approach and 5M learning strategies ? Abstrak Pendekatan saintifik merupakan salah satu pendekatan pembelajaran yang direkomendasikan dalam implementasi Kurikulum 2013. Dalam praktik pembelajaran, penggunaan pendekatan saintifik dilakukan dengan langkah-langkah (srategi) pembelajaran yang dikenal dengan strategi pembelajaran 5M yang terdiri atas: kegiatan mengamati, menanya, mengumpulkan data, mengasosiasi, dan mengomunikasikan (Permendikbud. No. 22 Tahun 2016). Strategi pembelajaran tersebut melatih peserta didik untuk melakukan kegiatan pembelajaran sebagaimana para saintis mengembangkan ilmu pengetahuan, walaupun tidak semua ilmu pengetahuan dikembangkan dengan cara tersebut. Diskusi antara pengusul pengabdian dengan mitra yaitu forum guru Ambarawa untuk menyelesaikan masalah, maka akan dilaksanakan pemecahan masalah. Pemecahan masalahan yang akan dilaksanakan, yaitu dengan cara melaksanakan pengabdian kepada masyarakat dengan judul Implementasi Pendekatan Saintifik Mata Pelajaran IPS Pada Forum Guru Ambarawa. Bertolak dari identifikasi permasalahan tersebut dirumuskan masalah sebagai berikut: (1) Bagaimanakah upaya melatih guru-guru membuat rancangan program pembelajaran dengan pendekatan saintifik dan strategi pembelajaran 5M?, (2) Bagaimanakah upaya melatih guru-guru melaksanakan pembelajaran dengan pendekatan saintifik dan strategi pembelajaran 5M?.